IMPROVEMENT OF SKIN HYDRATION PERCENTAGE BY INTERVENTION OF SHEEP PLACENTA CREAM IN ELDERLY POPULATION AT STW CIBUBUR PERIOD SEPTEMBER 2019 - Elizabeth, Jessica; Tan, Sukmawati Tansil; Firmansyah, Yohanes; Sylvana, Yana; Angelika, Michelle (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
The Population Reference Bureau (PRB) estimates that Indonesia will experience a population surge to 365.3 million by 2030, which will further affect the surge in the elderly population and increase health problems occurring in the elderly. One of the elderly health problems that often occur on the skin is skin hydration problem. Comercially available animal-derived placenta extracts are available in cream form for the purpose repairing skin components. Although the effects of placenta extract have been largely observed, no scientific studies have reported using sheep placenta extract to improve skin hydration levels. The purpose of this study was to look for an increase in the hydration level of elderly skin after intervention research in the form of sheep placenta extract cream. This research is a quasi-experimental study, with a total sampling method in the form of sampling. The study was conducted at the STW RIA Pembangunan Cibubur in September 2019. Sheep placenta cream is made by mixing 30 grams of placenta extract powder with 1000 grams of cream base. Skin hydration levels were measured using the Skin Analyzer Runve HL-611 corneometer. Respondents then apply the cream on the left forearm within 15 minutes after bathing. Skin hydration levels are measured every 1 week up to 4 times measurement. Changes in skin hydration in 51 respondents in a row from week 0 to week 3 were 35.10 ± 2.81, 35.96 ± 2.57, 36.28 ± 2.31, and 36.88 ± 2.30 . Analysis of statistical tests using the Repeated Measurement test showed a significant increase in hydration (p-value <0.001) between measurements due to intervention. The highest increase in hydration level was between the measurement of week-to-zero with the third week of 1.784 (0.276)%. As Conclusion, moisturizer from sheep placenta extract has been proven to increase the hydration level of elderly skin after using it for 3 weeks (p-value <0.05). Keywords: elderly; sheep placenta; skin hydrationABSTRAKPopulation Reference Bureau (PRB) memperkirakan bahwa Indonesia akan mengalami lonjakan populasi menjadi 365,3 juta jiwa pada tahun 2030 yang selanjutnya akan berdampak terhadap lonjakan populasi lanjut usia serta peningkatan permasalahan kesehatan yang terjadi pada lansia. Salah satu permasalahan kesehatan lansia yang sering terjadi pada kulit adalah masalah hidrasi kulit. Ekstrak plasenta yang diproses dari hewan sudah banyak tersedia secara komersial dalam bentuk krim dengan tujuan memperbaiki komponen kulit. Meskipun efek ekstrak plasenta sebagian besar telah dipelajari, namun belum ada studi ilmiah yang melaporkan penggunaan ekstrak plasenta domba untuk meningkatkan kadar hidrasi kulit. Tujuan penelitian ini adalah untuk mencari peningkatan kadar hidrasi kulit lansia setelah penelitian intervensi berupa krim ekstrak plasenta domba. Penelitian ini merupakan penelitian quasi eksperimental, dengan metode pengambilan sampel berupa total sampling. Penelitian dilakukan di Panti STW RIA Pembangunan Cibubur pada periode September 2019. Krim plasenta domba dibuat dengan mencampur 30 gram bubuk ekstrak plasenta dengan 1000 gram basis krim. Kadar hidrasi kulit diukur menggunakan korneometer Skin Analyzer Runve HL-611. Responden lalu mengoleskan krim plasenta domba pada tangan kiri 15 menit setelah mandi. Pengukuran status hidrasi kulit diukur setiap 1 minggu hingga 4 kali pengukuran. Perubahan kadar hidrasi kulit lengan kiri dari 51 responden berturut-turut pada minggu ke nol hingga minggu ketiga adalah sebesar 35,10 ± 2,81, 35,96 ± 2,57, 36,28 ± 2,31, dan 36,88 ± 2,30. Analisa uji statistik menggunakan uji Repeated Measurement didapatkan hasil kenaikan hidrasi yang bermakna (p-value < 0,001) antar pengukuran akibat pemberian intervensi berupa Krim Plasenta Domba. Peningkatan kadar hidrasi paling tinggi adalah antara pengukuran minggu ke nol dengan minggu ke tiga yaitu sebesar 1,784 (0,276)%. Sebagai kesimpulan, pelembab dari ekstrak plasenta domba terbukti dapat peningkatkan kadar hidrasi kulit lansia setelah pemakaian selama 3 minggu (p-value < 0,05). Kata Kunci: lansia; plasenta domba; status hidrasi